MENENTUKAN MODEL PERTUMBUHAN PENDUDUK PROVINSI SUMATERA BARAT - Febdian, Lindo; ., Efendi (Jurnal Matematika UNAND, 2013)
This research examines the population growth models which is used to estimate the total population of West Sumatra in the future. In this research, we use thesecondary data obtained from BPS (Central Bureau of Statistics). The data are population censuses in 1980, 1990, 2000 and 2010. The models in this study are linier model,geometry model, exponential model and logistic model. Based on the results absoluteerror of the growth models, logistic model with population growth is the best model toproject the population of West Sumatra in 2020.